"Capturing your audience": analysis of Twitter engagements between tweets linked with an educational infographic or a peer-reviewed journal article. (1st October 2020) - Barlow, Brooke; Barlow, Ashley; Webb, Andrew; Cain, Jeff
Abstract: Information represented through conventional text may fall short of capturing the attention and promoting engagement with today's digital audience. Transforming text into visual tools, such as infographics, has emerged as a simplified method of delivering information to attract a broader audience and enhance information dissemination. The first step to evaluate the potential value of infographics is to quantify their appeal and engagement rates over conventional text. This retrospective pilot analysis sought to evaluate the difference between engagement rates for tweets containing an of infographic compared to tweets containing a link to a peer-reviewed journal article. A total of 752 tweets were published within the study period; of these, 40 tweets met inclusion criteria. When engagement rates were compared, there was an increase in median engagement rates for tweets containing an infographic compared to a tweet linked to a peer-reviewed article at 10.97% (IQR 3.47%) and 5.33% (IQR 3.17%), respectively. This pilot study provides insight on the potential impact for infographics to enhance engagement rate, which may subsequently correlate with an increase in audience reach and readership. Prospective studies are needed to validate the utility of infographics in promoting scholarship publicity, learner engagement, and as a transferable pedagogical tool to educate medical practitioners.